Development of Vietnamese Medical Staff in the Period of Accelerated Industrialization and Modernization of the Country and (Asian Journal of Social Science Studies, 2020)
Medical staff holds a pivotal role in the Vietnamese health system, and is crucial to the efficiency and quality of health care services in Vietnam. It is their professional and dedicated work that is a permanent basis to guarantee protection of and care for people’s health in the provision of health care services to people in all regions, including remote areas, borders and islands. The continuous growth in the quantity and quality of health workers in Vietnam has affirmed the right leadership of the Communist Party of Vietnam in building this health workforce over the years.